Compassion matters in elite sports environments: Insights from high-performance coaches - Backman, E.; Hejl, C.; Henriksen, K.; Zettler, I. (Psychology of Sport and Exercise, 2024)
It is an open question to which degree compassion—noticing, engaging with, and acting to alleviate suffering in self and others—is (considered) advantageous in elite sports. Addressing this question, we herein provide insights into high-performance coaches` perceptions on the role of compassion in elite sports environments. Specifically, 12 coaches working at the highest level of their respective sport (in Denmark) partook in semi-structured interviews focusing on the utilization, implications, as well as barriers for implementing compassion in elite sports environments. Following a thematic analysis, three themes comprising various subthemes were identified and discussed. The first theme - Benefits of compassion - focuses on coaches` perception of the use and implications of compassion and comprises four subthemes: Compassion is important when times are tough; Compassion stimulates human connection; Compassion fosters unity in competitive environments; and Compassion promotes performance. The second theme - Increasing compassionate competence - focuses on how a compassionate approach can flourish and comprises three subthemes: Reflection; Awareness and knowledge; and Keeping up with the times. The third theme - Barriers to compassion - focuses on barriers to implementing and enhancing compassion in elite sports environments and comprises four subthemes: Compassion is soft; Power dynamics can stand in the way; Requires prioritization; and Performance outcome orientation. We conclude that while compassion (beyond self-compassion) can be beneficial in elite sports, coaches still perceive barriers for successful implementation, and that research should further investigate the outcomes and consequences of compassion in the elite sport context.